2017
DOI: 10.18559/soep.2017.7.3
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Properties of Selected Oils Used as Cosmetics Compounds

Abstract: Cosmetic vegetable oils for centuries have been objects of interest as ingredients of natural personal care products. Nowadays the trend for coming back to nature has caused their increased popularity in the preparation of natural cosmetics, soaps, and fragrance oils. Th e aim of the study was to evaluate the antimicrobial properties of 18 selected cold pressed cosmetic oils towards human pathogens. Th e antagonistic activity of cosmetic oils was assayed by the disc diff usion method. Indicator microorganisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Also, Marchwińska and Michocka [30] demonstrated that WGO had an antimicrobial activity against Streptococcus epidermidis and Pseudomonas aeruginosa. These organisms were reported as a regular cause of postoperative infection, and this action could accelerate the ulcer and wound healing.…”
Section: Discussionmentioning
confidence: 97%
“…Also, Marchwińska and Michocka [30] demonstrated that WGO had an antimicrobial activity against Streptococcus epidermidis and Pseudomonas aeruginosa. These organisms were reported as a regular cause of postoperative infection, and this action could accelerate the ulcer and wound healing.…”
Section: Discussionmentioning
confidence: 97%
“…Marchwi ńska et al [106] investigated the efficacy of 18 different cold-pressed cosmetic oils in terms of their ability to impede the proliferation of human pathogens. The antibacterial activity of cosmetic oils was assessed using the disc diffusion method.…”
Section: Seedsmentioning
confidence: 99%